Local outbreak of extended-spectrum β-lactamase SHV2a-producing Pseudomonas aeruginosa reveals the emergence of a new specific sub-lineage of the international ST235 high-risk clone. Issue 1 (January 2020) - Royer, G.; Fourreau, F.; Boulanger, B.; Mercier-Darty, M.; Ducellier, D.; Cizeau, F.; Potron, A.; Podglajen, I.; Mongardon, N.; Decousser, J.-W.
Summary: Background: Pseudomonas aeruginosa is a major bacterial pathogen responsible for hospital-acquired infections. Although its epidemiology is considered as non-clonal, certain international high-risk multidrug-resistant clones have been recognized. Aim: From the first report of an intra-hospital outbreak due to an SHV2a-producing P. aeruginosa strain, to describe the emergence of a new ST235-specific lineage harbouring this rare extended-spectrum β-lactamase (ESBL). Methods: Between May and October 2018, four patients hospitalized in the cardiovascular intensive care unit of a French teaching hospital were infected by a multidrug-resistant P. aeruginosa isolate. Serotype and antimicrobial susceptibility were tested; multi-locus sequence type (MLST), core genome MLST, and resistome were determined through whole genome sequencing. A phylogenetic analysis based on single nucleotide polymorphism was performed using available ST235 genomes. Findings: The four strains were susceptible to colistin, ciprofloxacin, ceftazidime–avibactam, and ceftolozane–tazobactam. bla SHV2a was identified in each genome of this ST235-O11 serotype cluster that showed an identical cgMLST profile (0–2 out of 4162 different alleles). The phylogenic analysis of 162 ST235 genomes showed that only four other strains harboured a bla SHV2a, originating from France and USA, clustering together although being different from the outbreak strains. Conclusions: Among the ST235 P. aeruginosa strains, a sub-lineage sharing a common genetic background and harbouring the bla SHV2a ESBL seems to emerge from different locations, yielding secondary local outbreaks.